Criminal Policy Against The Criminal Action Of Subsidized Fuel Hooking In Bongo Zero Village - Rizki Hidayat Palantu (Estudiante Law Journal, 2020)
The criminal policy against the criminal act of misuse of fuel oil and natural gas that occurred in the Bongo Nol gas station area was more focused on the "repressive" nature (suppression/eradication/suppression), after the crime or criminal act occurred. and is more of a preventive measure for the occurrence of crime, so the main target is to deal with the factors conducive to the occurrence of crime. The conducive factors, among others, are centered on problems or social conditions that are directly or indirectly. This effort is used primarily to direct that the objectives of business activities in the oil and gas sector can be carried out as optimally as possible to realize general welfare for all Indonesian people.The inhibiting factors in the enforcement of criminal law in cases of abuse of fuel oil and natural gas carried out by perpetrators in the Bongo Nol gas station area in this study were very much influenced by various factors, namely the legal factor itself such as the lack of detailed regulations governing criminal acts. abuse of fuel oil and natural gas committed by actors contained in Law No. 22 of 2001 concerning Oil and Gas, law enforcement factors where law enforcement processes will run properly when law enforcement officers carry out their duties by their respective codes of ethics, and the factor of a legal culture wherein dealing with criminal acts of abuse of fuel oil and natural gas committed by the perpetrators, law enforcement officers must have a strong mentality so that in processing cases of misuse of fuel oil and natural gas, especially at the Bongo Zero gas station, law enforcement officers can run pr process of law enforcement without sorting out who the perpetrators are behind the series of abuses of fuel oil and natural gas. Keywords: Oil Fuel, Law Enforcement, Criminal Law